Admission patterns and survival from status epilepticus in critical care in the UK: an analysis of the Intensive Care National Audit and Research Centre Case Mix Programme database. (6th November 2019) - Damian, M. S.; Ben‐Shlomo, Y.; Howard, R.; Harrison, D. A.
Abstract : Background and purpose: Factors influencing the outcome after the critical care unit (CCU) for patients with status epilepticus (SE) are poorly understood. Survival for these patients was examined to establish (i) whether the risk of mortality has changed over time and (ii) whether admission to different unit types affects mortality risk over and above other risk factors. Methods: The Intensive Care National Audit and Research Centre database and the Case Mix Programme database (January 2001 to December 2016) were analysed. Units were defined as neuro‐CCU (NCCU), general CCU with 24‐h neurological support (GCCU‐N) or general CCU with limited neurological support (GCCU‐L). Results: There were 35 595 CCU cases of SE with a 3‐fold increase over time (4739 in 2001–2004 to 14 166 in 2013–2016). More recent admissions were older and were more often unsedated on admission. Mortality declined for all units although this was more marked for NCCUs (8.1% in 2001–2004 to 4.4% in 2013–2016 compared to 5.1% and 4.1% for GCCU‐L). Acute hospital mortality was two to three times higher than CCU mortality although this has also declined with time. GCCU‐L appeared to have lower mortality than NCCUs (odds ratio 0.84, 95% confidence interval 0.72, 0.98) but after post hoc adjustment for case mix there were no differences. Older age and markers of seriousness of morbidity were all associated with increased mortality risk. Conclusions: The number of patients admitted to a CCU for SE is rising but critical care and acute hospital mortality is decreasing. Patients treated in an NCCU have higher mortality but this is explicable by more severe underlying disease.